(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
By sharing the experiences of the process of putting together La prima volta, which was the first phase of the solo performance The Nightmare of the Butterfly, created by this author and directed by Julia Varley (Odin Teatret), we discuss the unfolding of the theatrical tradition based on the assumptions of Theater Anthropology in the pedagogy of the Odin Teatret group, highlighting creation based on Actress and actor’s dramaturgy.